Laparoscopic management of gastric outlet obstruction due to gastric lipoma: A case report. - Akhtar, Murtaza; Chandak, Kanhaiya; Kumar, Kanav (Indian Journal of Case Reports, 2018)
A gastric lipoma is a rare entity and accounts for 2